Thermal conductive sheet
Patent Information
- Application Number
- JP2025111082
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2025-06-30
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167359000001_ABST
Abstract
Description
Background Art
[0001] The present invention relates to a thermally conductive sheet.
[0002] Thermally conductive sheets that are disposed between a heating element and a heat dissipation component and efficiently transfer heat from the heating element to the heat dissipation component are known. For example, the technique disclosed in Patent Document 1 is one such example. In recent years in particular, high-density electronic devices have been widely used, and such electronic devices generate a large amount of heat during operation, so the requirements for the thermal conductivity of thermally conductive sheets have further increased.
[0003] Such thermally conductive sheets are required to adhere closely to irregularities on the surfaces of heating elements and heat dissipation components in order to conduct heat efficiently. For this reason, silicone-based thermally conductive sheets, which have excellent heat resistance, flexibility, and high thermal conductivity of the resin itself, are sometimes used as thermally conductive sheets. However, with prolonged use of silicone-based thermally conductive sheets, there are concerns that oil contained in the resin may leak out (oil bleed-out), or siloxane gas may be generated to form an insulator, which may adhere to electrical contacts and cause poor contact.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
[0005] For this reason, heat dissipation sheets that do not use silicone-based resins have been proposed. Such heat dissipation sheets are configured to include a filler and a resin. As the filler, ceramic particles with high thermal conductivity such as Al₂O₃, AlN, SiN, h-BN, and C are suitably used, and as the resin, substances for maintaining the sheet shape such as acrylic resin, polyimide resin, and epoxy resin are used.
[0006] On the other hand, these resins have inferior thermal conductivity compared to the resins used in the aforementioned silicone-based thermal conductive sheets. Therefore, in heat dissipation sheets that do not use silicone-based resins, there has been a need for methods to further improve thermal conductivity.
[0007] Based on the above circumstances, and after various studies, the present invention was found to change the thermal conductivity of the heat conductive sheet produced by varying the shape of the filler used in the heat conductive sheet. The present invention is based on this finding.
[0008] The present invention was made against the above circumstances, and its objective is to provide a heat conductive sheet using fillers, in which the thermal conductivity of the heat conductive sheet can be improved by making the particle shape polyhedral and varying the size of the particles. [Means for solving the problem]
[0009] In other words, the gist of the first invention is a heat-conducting sheet made by including a resin and a plurality of fillers having different shapes as raw materials, characterized in that the fillers include spherical particles and polyhedral particles.
[0010] Furthermore, the gist of the second invention is that, in the first invention, the polyhedral particles are 10 vol% or more and 40 vol% or less in volume ratio to the total filler.
[0011] The gist of the third invention is that, in the first invention, the filler comprises first particles having a D50 diameter of 65 μm or more and 90 μm or less, and second particles having a D50 diameter of 3 μm or more and 7 μm, wherein the first particles are spherical particles, the second particles include polyhedral particles, and the first particles constitute 4 vol% or more and less than 50 vol% of the total volume of the filler.
[0012] The gist of the fourth invention is that, in the third invention, the proportion of polyhedral particles in the second particle is 10 vol% or more and 40 vol% or less in volume ratio to the total filler.
[0013] The gist of the fifth invention is that, in the third invention, the filler comprises a third particle having a D50 diameter of 0.1 μm or more and 1 μm or less, and a fourth particle having a D50 diameter of 25 μm or more and 45 μm or less.
[0014] The gist of the sixth invention is that, in the fifth invention, the second particle is 5 vol% or more and 50 vol% or less in volume ratio to the total filler, the third particle is 5 vol% or more and 50 vol% or less in volume ratio to the total filler, and the fourth particle is 10 vol% or more and 45 vol% or less in volume ratio to the total filler.
[0015] The gist of the seventh invention is that, in the first invention, the resin is 15 vol% or more and 25 vol% or less in volume ratio to the total raw materials. [Effects of the Invention]
[0016] According to the first invention, the thermal conductive sheet contains spherical particles and polyhedral particles, which are fillers having multiple different shapes, and thus the thermal conductivity can be improved.
[0017] According to the second invention described above, since the polyhedral particles are contained in an amount of 10 vol% to 40 vol% by volume relative to the total filler, the thermal conductivity of the thermal conductive sheet can be improved.
[0018] According to the third invention, the filler comprises first particles having a D50 diameter of 65 μm or more and 90 μm as spherical particles, and second particles having a D50 diameter of 3 μm or more and 7 μm as polyhedral particles, wherein the first particles constitute 4 vol% or more and less than 50 vol% of the total volume of the filler, thereby improving the thermal conductivity of the thermal conductive sheet.
[0019] According to the fourth invention, the proportion of polyhedral particles in the second particles is 10 vol% or more and 40 vol% or less by volume ratio relative to the entire filler, so that a suitable sheet can be obtained when the filler contains polyhedral particles and spherical particles.
[0020] According to the fifth invention, the filler includes third particles having a D50 diameter of 0.1 μm or more and 1 μm or less and fourth particles having a D50 diameter of 25 μm or more and 45 μm or less, so that the filler can be composed of a plurality of types of filler with different particle sizes.
[0021] According to the sixth invention, the first particles account for 4 vol% or more and less than 50 vol% by volume ratio relative to the entire filler, the second particles account for 5 vol% or more and 50 vol% or less by volume ratio relative to the entire filler, the third particles account for 5 vol% or more and 50 vol% or less by volume ratio relative to the entire filler, and the fourth particles account for 10 vol% or more and 45 vol% or less by volume ratio relative to the entire filler, so that a suitable sheet can be obtained even when the filler contains a plurality of types of particles with different particle sizes.
[0022] According to the seventh invention, the resin accounts for 15 vol% or more and 25 vol% or less by volume ratio relative to the entire raw material, so that the heat conductive sheet has excellent formability. Brief Description of the Drawings
[0023] [Figure 1] It is a diagram illustrating the manufacturing process of the heat conductive sheet of the present invention. [Figure 2] It is a diagram illustrating the outline of the roll forming machine used in the rolling step of Figure 1. [Figure 3] This is an example of a backscattered electron image of the cross section of the heat conductive sheet in the present example. [Figure 4] It is a diagram comparing the heat conductive sheets of the present example and the comparative example. [Figure 5] It is another diagram comparing the heat conductive sheets of the present example and the comparative example. [Figure 6] This is still another diagram for comparing the thermally conductive sheets of the present example and the comparative example. [Figure 7] This is still another diagram for comparing the thermally conductive sheets of the present example and the comparative example. [Figure 8] This is still another diagram for comparing the thermally conductive sheets of the present example and the comparative example. [Modes for Carrying Out the Invention]
[0024] Figure 1 is a diagram illustrating the production process of the thermally conductive sheet of the present invention. In Figure 1, first, a kneading step P1 is performed. In this kneading step P1, the first particles, second particles, third particles and fourth particles as fillers, which are the raw materials of the thermally conductive sheet, are mixed with the resin material. As the filler, at least the first particles and the second particles having a plurality of different shapes are used, and further, the third particles may be used, or the third particles and the fourth particles may be used. The filler is made of an inorganic material, for example, a known ceramic material, and more specifically, aluminum nitride (AlN), alumina (Al₂O₃) or the like is used. In addition, a thermosetting resin is used as the resin, and specifically, for example, an acrylic resin is used.
[0025] These fillers and the resin are kneaded by a vacuum mixer (in the examples described later, ARV-200, a planetary centrifugal mixer manufactured by Thinky Corporation, was used) to produce a clay mass.
[0026] In the subsequent rolling step P2, the clay mass obtained in the kneading step P1 is rolled by a roll forming machine to be formed into a sheet shape.
[0027] Figure 2 is a schematic diagram showing an example of a roll forming machine 50 used in the rolling process P2. The clay 40 produced in the mixing process P1 is supplied between a pair of metal rolls 52. The pair of metal rolls 52 are spaced apart, and the pair of metal rolls 52 are rotated to push the clay 40 downwards as shown in Figure 2. This predetermined spacing and the rotation speed of the metal rolls 52 are predetermined to correspond to the thickness of the sheet 42 to be produced. The thickness of the sheet 42 is predetermined to be, for example, 1 mm. In this way, the clay is rolled and formed into a sheet 42 of the desired thickness.
[0028] Furthermore, in the roll forming machine 50 shown in Figure 2, a film 54 is provided between the clay 40 and a pair of metal rolls 52. The film 54 is prepared in advance by being wound onto a roll 53, and is pulled out from the roll 53 and supplied as the metal rolls 52 rotate. As a result, the clay 40 and the metal rolls 52 do not come into direct contact during rolling, so that the surface of the sheet 42 produced is protected while rolling is performed.
[0029] Returning to Figure 1, in the molding process P3, the sheet 42 obtained in the rolling process P2 is cut to a predetermined length or die-cut using a predetermined mold to obtain a sheet 42 of the desired shape.
[0030] In the heating step P4, the sheet 42 of the desired shape obtained in the molding step P3 is heat-treated under predetermined conditions. This heat treatment is carried out at a temperature and heating time predetermined according to the material and proportion of the raw materials, such as the resin and filler. For example, in the case of the example of a 1 mm thick heat-conducting sheet described later, the heat treatment conditions are set to 110°C and 20 minutes.
[0031] Figure 3 is a backscattered electron image of the cross-sectional structure of the thermal conductive sheet 30 produced by the above process. As shown in this figure, the thermal conductive sheet 30 in this figure contains elongated h-BN (hexagonal boron nitride) particles, which are shown in black. It can be seen that the polyhedral alumina particles (second particles) 32 are in surface contact with the elongated h-BN particles. In other words, the contact area between the fillers is larger than when only spherical particles 34 were present. This makes it possible to efficiently transfer heat between the filler particles 32 and 34, improving the overall thermal conductivity of the sheet 30.
[0032] Experimental example The following describes tests conducted by the inventors of the present invention to confirm its effectiveness, but the present invention is not limited to these test results.
[0033] In this experiment, as described later, 1 mm thick sheets were prepared by varying the composition of the raw materials for the thermal conductive sheets. The preparation was carried out according to the procedure shown in Figure 1 above. The thermal conductivity of the prepared thermal conductive sheets was measured, evaluated, and compared. A Lesca TCM1001 thermal conductivity measuring device was used to measure the thermal conductivity. The measurement conditions for thermal conductivity were those specified based on ASTM (American Society for Testing and Materials) standard D5470 and JIS (Japanese Industrial Standards) H7903, etc. In addition, it was evaluated whether a clay base could be prepared at the completion of the mixing process P1 in the preparation procedure shown in Figure 1, and whether a sheet shape could be formed at the completion of the rolling process P2.
[0034] Figure 4 is a diagram evaluating the difference in thermal conductivity of thermal conductive sheets obtained from multiple experimental results, depending on the presence or absence of polyhedral particles 32. In Figures 4 to 8 below, the comparative examples do not meet the requirements of the present invention and are not considered examples. In Figures 4 to 8, the "Clay Formation" column indicates whether or not clay was produced at the completion of the mixing process P1, marked with ○ or ×, and the "Sheet Formation" column indicates whether or not a sheet shape was formed at the completion of the rolling process P2, marked with ○ or ×. In cases where clay formation is marked with ×, a "-" is indicated because sheet formation could not be evaluated. In Figures 4 to 8, the first to fourth particles are ceramic particles of different particle sizes used as fillers, and correspond to the first to fourth particles of the present invention, respectively. In this experimental example, only the second particle may contain polyhedral particles 32, while the first, third, and fourth particles are composed of spherical particles 34. Furthermore, the polyhedral particles 32 are not limited to a specific number of faces, but are intended to be manufactured in such a way that their surface is composed of multiple planes. Also, the spherical particles 34 are not limited to a polyhedral shape, but may be ellipsoidal or teardrop-shaped. In addition, in this invention, the D50 diameter refers to the value corresponding to 50% of the cumulative value from the smallest particle size in the volume-based particle size distribution based on laser diffraction scattering.
[0035] In Figure 4, Comparative Examples 1 to 5 all contain first to fourth particles with different particle sizes, but the first to fourth particles are all composed of spherical particles 34. Of these, Comparative Example 1 could not be formed into soil. On the other hand, Comparative Examples 2 to 5 were able to be formed into soil and sheets. That is, as shown in Comparative Examples 2 to 5, sheet formation was possible when the amount of resin was 20 to 35 vol% of the total raw material. On the other hand, Examples 1 and 2 are different in that all of the second particles are changed from spherical particles 34 to polyhedral particles 32. Also, Examples 1 and 2 differ in that the first particles are alumina (Al2O3) and aluminum nitride (AlN). Both Experimental Examples 1 and 2 were able to be formed into soil and sheets. In Examples 1 and 2, sheet formation was possible when the amount of resin was 17 to 25 vol% of the total raw material. In general, a smaller amount of resin makes it easier for the fillers to come into contact with each other, so an improvement in thermal conductivity can be expected. The thermal conductivity of the thermal conductive sheets in Comparative Examples 2 to 5 was 2.2 to 5.4 W / m·K. On the other hand, the thermal conductivity of the thermal conductive sheets in Examples 1 and 2 was 6.4 to 6.6 W / m·K, which is a significant improvement compared to the thermal conductivity of Comparative Examples 1 to 5.
[0036] Figure 5 shows the relationship between the amount of polyhedral particles 32 added and the thermal conductivity of thermal conductive sheets obtained from multiple experimental results. In Examples 3, 4, 1, 5, and 6, the ratio of polyhedral particles 32, which are the second particles, to the total filler was varied in the order of 10, 15, 21, 30, and 40 vol%, respectively, and the thermal conductivity of the fabricated thermal conductive sheets was measured. In addition, as Comparative Example 3, an example in which the second particles consisted entirely of spherical particles 34 was also measured.
[0037] As shown in Figure 5, the thermal conductivity is improved when polyhedral particles 32 are included in the second particle compared to when they are not included. Furthermore, it can be seen that the value of thermal conductivity increases (thermal conductivity improves) as the proportion of polyhedral particles 32 in the second particle increases. Preferably, this trend is observed in the region where the proportion of polyhedral particles 32 in the second particle is less than 50 vol%, and the value of thermal conductivity increases (thermal conductivity improves) as the proportion of polyhedral particles 32 in the second particle increases. As shown in Figure 5, in this embodiment, thermal conductive sheets made with a relatively small amount of resin all show suitable thermal conductivity, while comparative examples made with a similar amount of resin show relatively inferior thermal conductivity.
[0038] Figure 6 is a diagram evaluating the relationship between the amount of first particles added and the resulting heat conductive sheets obtained from multiple experimental results. In Examples 7, 2, and 8, heat conductive sheets were prepared by varying the proportion of first particles to the total filler, in the order of 30%, 32.5%, and 40 vol%, respectively. Similarly, in Comparative Examples 6 and 7, heat conductive sheets were prepared when the proportion of first particles to the total filler was 20% and 50 vol%, respectively.
[0039] As shown in Figure 6, Examples 7, 2, and 8, which correspond to the embodiments of the present invention, were all able to produce thermal conductive sheets and showed a suitable thermal conductivity of 6.5 to 7.0 W / m·K. However, Comparative Example 6, which deviates from the embodiments of the present invention, could not be formed into clay, and Comparative Example 7 could not be formed into a sheet. In both cases, thermal conductive sheets could not be produced.
[0040] Figure 7 shows the evaluation of a thermal conductive sheet obtained from multiple experimental results when particles other than the first to fourth particles are included as fillers. In the previously mentioned examples, the fillers were composed of a combination of the first to fourth particles, which have different particle sizes and shapes. On the other hand, examples 9 and 10 in Figure 7 have compositions that further include particles with a D50 diameter of approximately 50 μm in addition to those. Specifically, both examples 9 and 10 have compositions that include spherical alumina particles with a D50 diameter of 50.79 μm at concentrations of 10 vol% and 5 vol%, respectively, relative to the total filler.
[0041] As shown in Figure 7, both Examples 9 and 10 are capable of producing thermally conductive sheets and exhibit superior thermal conductivity compared to the comparative example. Therefore, the effects of the present invention can be obtained even when particles of different particle sizes are included as fillers, in addition to the first to fourth particles included within the scope of the present invention.
[0042] Figure 8 illustrates Examples 11 to 13, in which the particle sizes (D50 diameter) of the second polyhedral particle 32, the third spherical particle 34, and the fourth spherical particle 34 contained in the filler differ from those of Examples 1 to 10 described above. Specifically, Example 11 differs from the raw material composition of Examples 1 to 10 in that, while in Examples 1 to 10 the D50 diameter of the second polyhedral particle 32 was 5.92 μm, the D50 diameter of the third spherical particle 34 was 0.68 μm or 0.89 μm, and the D50 diameter of the fourth spherical particle 34 was 40.15 μm, in Example 11 the D50 diameter of the second polyhedral particle 32 was 6.04 μm and the D50 diameter of the fourth spherical particle 34 was 27.84 μm, and they are otherwise common. Furthermore, Example 12 is an example in which the D50 diameter of the second polyhedral particle 32 is changed from 5.92 μm in Example 11 to 3.68 μm, compared to the raw material composition of Example 11. Example 13 is an example in which the D50 diameter of the third spherical particle 34 is changed from 0.89 μm in Example 12 to 0.365 μm, compared to the raw material composition of Example 12.
[0043] As shown in Figure 8, thermal conductive sheets can also be fabricated in Examples 11 to 13, exhibiting superior thermal conductivity compared to the comparative examples. Therefore, the effects of the present invention can be obtained when the particle size of the filler included within the scope of the present invention is met.
[0044] According to the thermal conductive sheet of this embodiment, since it is a thermal conductive sheet that contains spherical particles 34 and polyhedral particles 32 which are fillers having multiple different shapes, the thermal conductivity can be improved.
[0045] According to the thermal conductive sheet of this embodiment, the polyhedral particles 32 of the second particle are contained in an amount of 10 vol% to 40 vol% by volume relative to the total filler, thereby improving the thermal conductivity of the thermal conductive sheet.
[0046] According to the thermal conductive sheet of this embodiment, according to the third invention, the filler includes first particles with a D50 diameter of 65 μm or more and 90 μm as the spherical particles 34, and second particles with a D50 diameter of 3 μm or more and 7 μm as the polyhedral particles 32, and the first particles constitute 4 vol% or more and less than 50 vol% of the total volume of the filler, thereby improving the thermal conductivity of the thermal conductive sheet.
[0047] According to the heat-conducting sheet of this embodiment, according to the fourth invention, the proportion of polyhedral particles 32 in the second particles is 10 vol% or more and 40 vol% or less in volume ratio to the total filler, so a suitable sheet can be obtained when the filler contains polyhedral particles 32 and spherical particles 34.
[0048] According to the thermal conductive sheet of this embodiment, according to the fifth invention, the filler includes third particles with a D50 diameter of 0.1 μm or more and 1 μm, and fourth particles with a D50 diameter of 25 μm or more and 45 μm, so it can be composed of fillers of multiple particle sizes.
[0049] According to the heat-conducting sheet of this embodiment, according to the sixth invention, the first particles have a volume ratio of 4 vol% or more and less than 50 vol% of the total filler, the second particles have a volume ratio of 5 vol% or more and 50 vol% or less of the total filler, the third particles have a volume ratio of 5 vol% or more and 50 vol% or less of the total filler, and the fourth particles have a volume ratio of 10 vol% or more and 45 vol% or less of the total filler. Therefore, a suitable sheet can be obtained even when the filler contains particles of multiple particle sizes.
[0050] According to the thermal conductive sheet of this embodiment, and according to the seventh invention, the resin is present in a volume ratio of 15 vol% to 25 vol% relative to the total raw materials, so the thermal conductive sheet has excellent moldability.
[0051] Although the present invention has been described in detail above with reference to tables and drawings, the present invention can be implemented in other embodiments, and various modifications can be made without departing from its spirit.
[0052] For example, in the above-mentioned embodiment, alumina or aluminum nitride was used as the filler, but other known ceramic particles can be used. For example, oxide ceramics include ceramic materials containing oxides of various metal elements. Examples of such oxide ceramics include zirconia (ZrO2), yttria (Y2O3), and talc (Mg2Si4O3). 10Examples include hematite (Fe2O3), chromia (Cr2O3), titania (Ti2O), magnesia (MgO), silica (SiO2), calcia (CaO), ceria (CeO2), tin oxide (TO;SnO2) ferrite (MnFe2O4), spinel (MgAl2O4), zircon (ZrSiO4), barium titanate (BaTiO3), lead titanate (PbTiO3), fluorosterite (Mg2SiO4), phosphorus-doped tin oxide (PTO), antimond-doped tin oxide (ATO), tin-doped indium oxide (ITO), etc. The ceramic particles 10 may contain one or more of the above-mentioned oxide ceramics. In other words, the ceramic particles 10 may contain composite metal oxides such as steatite (MgO·SiO2), cordierite (2MgO·2Al2O3·5SiO2), and mullite (3Al2O3·2SiO2). Furthermore, as non-oxide ceramics, the ceramic material may contain nitrides, carbides, borides, silicides, phosphate compounds, etc. of various metal elements. Specifically, examples include titanium nitride (TiN), gallium nitride (GaN), carbon nitride (CNx), and sialon (Si3N4-AlN-Al2O3 solid solution). Examples of carbide ceramics include tungsten carbide (WC), chromium carbide (CrC), vanadium carbide (VC), niobium carbide (NbC), molybdenum carbide (MoC), tantalum carbide (TaC), titanium carbide (TiC), zirconium carbide (ZrC), hafnium carbide (HfC), silicon carbide (SiC), and boron carbide (B4C). Examples of boride ceramics include molybdenum boride (MoB), chromium boride (CrB2), hafnium boride (HfB2), zirconium boride (ZrB2), tantalum boride (TaB2), and titanium boride (TiB2). Examples of silicified ceramics include zirconium oxide silicate, hafnium oxide silicate, titanium oxide silicate, lanthanum oxide silicate, yttrium oxide silicate, titanium oxide silicate, tantalum oxide silicate, and tantalum oxynitride silicate. Examples of phosphate compounds include hydroxyapatite and calcium phosphate.
[0053] Furthermore, although acrylic resin was used as the resin in the above-described examples, other known resins may be used. For example, natural polymer compounds such as carrageenan and xanthan gum, cellulosic polymers such as carboxymethylcellulose, acrylic resins, epoxy resins, phenolic resins, amine resins, alkyl resins, etc. may be used.
[0054] Furthermore, in the above-described examples, the raw materials for the thermal conductive sheet included at least ceramic particles and resin, but other materials may also be included. Specifically, for example, known dispersants, plasticizers, defoamers, release agents, antioxidants, thickeners, porosity-forming materials, etc., can be used as additives.
[0055] It should be noted that the above is merely one embodiment, and although other examples are not provided, the present invention can be implemented in various modified and improved forms based on the knowledge of those skilled in the art, without departing from its spirit. [Explanation of Symbols]
[0056] 30: Thermal conductive sheet 32: Polyhedral particles 34: Spherical particles
Claims
1. A thermal conductive sheet made by incorporating fillers and resin having multiple different shapes as raw materials, The filler includes spherical particles and polyhedral particles. A heat-conducting sheet characterized by [feature].
2. The polyhedral particles are present in a volume ratio of 10 vol% to 40 vol% relative to the total filler. A thermal conductive sheet according to claim 1, characterized by the above.
3. The aforementioned filler is, A first particle with a D50 diameter of 65 μm or more and 90 μm or less, It includes a second particle with a D50 diameter of 3 μm or more and 7 μm or less, The first particle is the spherical particle, The second particle includes the polyhedral particle. The first particle is present in a volume ratio of 4 vol% or more and less than 50 vol% relative to the total filler. A thermal conductive sheet according to claim 1, characterized by the above.
4. The proportion of polyhedral particles in the second particle is 10 vol% or more and 40 vol% or less in volume relative to the total filler. A thermal conductive sheet according to claim 3, characterized by the above.
5. The aforementioned filler is, A third particle with a D50 diameter of 0.1 μm or more and 1 μm or less, It includes a fourth particle with a D50 diameter of 25 μm or more and 45 μm or less. A thermal conductive sheet according to claim 3, characterized by the above.
6. The second particle is present in a volume ratio of 5 vol% to 50 vol% relative to the total filler. The third particle is present in a volume ratio of 5 vol% to 50 vol% relative to the total filler. The fourth particle is present in a volume ratio of 10 vol% to 45 vol% relative to the total filler. The thermal conductive sheet according to claim 5, characterized by the above.
7. The resin is present in a volume ratio of 15 vol% to 25 vol% relative to the total raw materials. A thermal conductive sheet according to claim 1, characterized by the above.
Citation Information
Patent Citations
Green sheet and method for producing the same
JP2022097775A